Optimizing Public Service Through E-Government Services (The Case of Public Service in South Jakarta Municipality) - WULANDARI, FLORENTINA; ANSHORI, YULI (Jurnal Studi Pemerintahan, 2012)
The development of information technology and public administration paradigms thatemphasize services for the benefit of society has affected the strategic efforts of e-Gov in Indonesia. Forthat, there is a need to create qualified, competitive, effective and efficient of the public services.Indonesia’s E-Gov Policy has been applying principles of good governance and information technologyto serve and interact with the community. Some local governments, including South JakartaMunicipality has been implementing e-Gov to optimize public service. e-Gov in South JakartaMunicipality is reflected on the implementation of a management information technology to improveservices to the community by creating a web site, namely http://selatan.jakarta.go.id/. The informationpresented in South Jakarta Municipality website includes tourism, local regulations, and otherinformation of Municipality of South Jakarta.